PENGARUH PERENCANAAN PAJAK, MANAJEMEN LABA, PROFITABILITAS, LEVERAGE DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Indi Nervilia; Deni Sunaryo (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
The research has goal to know the effect of tax planning, earnings management, profitability, leverage, and good corporate governance on firm value.Method of research is quantitative method. The research population was 141 companies, and took sample 42 companies or 126 research samples by using purposive sampling. Form of this data was financial report and god from Indonesia Stock Exchange in official site www.idx.co.id, and analyzed by SPSS 23 version. The analysis technique has been done by using logistic regressions, t test, and coefficient determination.Based on the result of regression analysis of profitability and independent commissioner influence to firm value. Tax planning, earnings management, leverage, institutional ownership, managerial ownership, and audit quality has no effect on firm value